Penerapan SAK-EMKM Pada Kesenian Jaranan Turonggo Bimo Kertosono Sebagai Simbol Budaya - Martinus Sony Erstiawan (BIP's JURNAL BISNIS PERSPEKTIF, 2020)
Art groups that have the soul of art in Indonesia are a group of micro, small, and medium entities (EMKM) that can use financial accounting standards for micro, small, and medium entities (SAK-EMKM). One of them is the art group which is still a symbol of cultural preservation, namely jaranan art. Financial management (recording, presentation, and disclosure) in the art of the networking requires the intention and practice as often as possible, so as to produce a simple financial report following accounting standards in force in Indonesia. This essay has the purpose of using a descriptive study of the application of SAK-EMKM to be applied to arts groups in Indonesia.